Tracking student performance in introductory programming by means of machine learning - Khan I.; Al Sadiri A.; Ahmad A.R.; Jabeur N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Big data; Decision trees; Education computing; Learning algorithms; Learning systems; Machine learning; Smart city; Students; Trees (mathematics); Educational data mining; Educational institutions; Hidden patterns; Introductory programming; Introductory programming course; Student performance; Student's performance; Weka; Data mining